Analysis on the effects of ecological conservation redline policies in the Pearl River Delta area, China - Wang, Xin; Zhang, Zhe; Hao, Haiguang; Zhang, Chao; Wang, Ding (Frontiers in Ecology and Evolution, 2023)
The ecological conservation redline (ECR) policies conducted in China is an important innovation to protect biodiversity, safeguard ecological security, and achieve sustainable development. The Pearl River Delta (PRD) area implemented the ECR policies in 2005. For this time point, this study examined the contrast between the 15 years before and after it. In the meantime, this study also revealed the ECR policies’ effects by comparing land use change, landscape pattern index, and habitat quality inside (IECR) and outside (OECR) the ECR area. The results suggest that: (1) ECR area has served as an ecological barrier in maintaining the stability of natural ecosystems. (2) Over the past 30 years, the PRD area significantly changed land use types and ecosystems, mainly concentrated in the central plains and estuaries. Specifically, in the IECR, land use change was relatively stable, with a decrease of 0.05% and 0.57% in ecological land and an increase of 0.28% and 0.68% in construction land before and after 2005. In contrast, the OECR area land use changed dramatically, with a decrease of 0.37% and 1.36% in ecological land and an increase of 7.06% and 5.02% in construction land before and after 2005. (3) A general trend of landscape fragmentation exists in the study area. The contagion (CONTAG) in the IECR area was higher than in the OECR. The Shannon’s diversity index (SHDI) in the IECR is lower than in the OECR area, which indicates a high degree and rapid landscape fragmentation in the OECR area. (4) Over 85% of the IECR scale had a habitat quality of 0.8–1, While the OECR area had an almost half scale with a habitat quality of 0–0.2. To conclude, the implementation of ECR policies has provided an experience for ecological protection in other regions.